P2Y6 수용체 길항제의 파골세포 분화 촉진 효과 규명 - 노아롱새미(A Long Sae Mi Noh); 문미란(Miran Moon); 임미정(Mijung Yim) (Yaghag-hoi-ji, 2015)
P2Y receptors, a type of P2 receptor family, are G-protein coupled receptors and 8 subtypes have been characterized (P2Y1, P2Y2, P2Y4, P2Y6, P2Y11-14). Recently, several studies have shed light on the role of P2Y receptors in bone biology. Among them, little is known on the role of P2Y6 receptor on osteoclast differentiation. Thus, we investigated the role of P2Y6 receptor on osteoclastogenesis using P2Y6 receptor selective antagonist, MRS 2578. When osteoblasts and bone marrow cells were co-cultured in the presence of VitD3 and PGE2, P2Y6 antagonist increased the formation of TRAP positive osteoclasts. To elucidate the target cells of P2Y6 antagonist, we first checked the effect of MRS 2578 on osteoblasts. Treatment of MRS 2578 did not affect OPG : RANKL mRNA ratio in osteoblasts. Next, we checked the effects of P2Y6 antagonist on osteoclast precursors using mouse bone marrow macrophages (BMMs). Addition of MRS 2578 increased the number of osteoclasts in RANKL-treated BMMs. Although P2Y6 antagonist had no effect on RANKL-induced NFATc1, c- Fos and MafB expression levels, it significantly stimulated RANKL-induced Blimp1 mRNA expression in BMMs. Taken together, these data indicate that P2Y6 antagonist increases osteoclast formation by upregulation of Blimp1 expression. KCI Citation Count: 0